Variasi Konsentrasi Pektin Terhadap Kualitas Selai Labu Kuning (Cucurbita moschata Durch) - Aldi Aldi; Akhyar Ali; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aimed to get the best concentration in manufacturing pumpkin jam (Cucurbitamoschata Durch). The testing method was randomized design with 5 treatments and 3 multiplications. The treatment in this research were A1 (pectin 0.5% and 99.5% pumpkin porridge), A2 (pectin 0.75% and 99.25% pumpkin porridge), A3 (pectin 1% and 99% pumpkin porridge), A4 (pectin 1.25% and 98,75% pumpkin porridge) and A5 (pectin 1,5% and 98,5% pumpkin porridge). The data were analyzed statistically using ANOVA and DNMRT at 5% level. Thus, it had been proven that the addition of pectin significantly affected the results of the analysis. The choosen treatment consisted of 1.5% pectin, 98.5% pumpkin porridge (A5) which containt 46.54% water, 0.125% ash, 66.10% sucrose, 0.49% crude fiber and 73.01% dissolved solids. The description and hedonic results proved thatthe scent and taste was that of a yellow squash, with softtexture and brownish yellow in color, which overall were preferred by the panelists. Keywords: jam, pectin, yellow squash, pumpkin.